The Effect Of Organizational Culture, Work Competency and Discipline on Work Spirit That Impact on Employee Performance at The Business of Transportation in West Jakarta - Ibnu Sina; Denok Sunarsi (Program Pascasarjana Universitas Negeri Makassar, 2021)
This study aims to determine the effect of organizational culture, competence and work discipline on work morale which has an impact on employee performance at the West Jakarta Transportation Agency. The method used is explanatory research with a sample of 125 respondents. The analysis technique uses statistical analysis with regression testing, coefficient of determination and hypothesis testing. The results of this study that organizational culture has a significant effect on work morale by 25.9%, hypothesis testing obtained a significance of 0.000 <0.05. Competence has a significant effect on work morale by 39.0%, hypothesis testing obtained a significance of 0.000 <0.05. Work discipline has a significant effect on work morale by 26.7%, hypothesis testing obtained a significance of 0.000 <0.05. Organizational culture, competence and work discipline simultaneously have a significant effect on work morale by 48.9%, hypothesis testing is obtained a significance of 0.000 <0.05. Work enthusiasm has a significant effect on employee performance by 38.8%, hypothesis testing obtained a significance of 0.000 < 0 ,05..